PENGARUH FAKTOR TEKANAN KERJA, OTONOMI KERJA, LINGKUNGAN KERJA, DAN BUKTI FISIK, TERHADAP KEPUASAN PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PEMERINTAH KOTA TANJUNGPINANG - Eko Murti Saputra (Jurnal Inovasi Penelitian, 2021)
This study aims to determine and analyze the influence of work pressure factors, work autonomy, work environment, and physical evidence on the satisfaction of employees of the Department of Population and Civil Registration of the Tanjungpinang City Government. The method chosen is quantitative research by distributing questionnaires. The sample of this research is all employees of the Department of Population and Civil Registration of the Tanjungpinang City Government, totaling 39 employees with the status of Civil Servants. The data analysis method used is descriptive analysis and multiple linear regression analysis, t test and F test. The results of this study indicate that simultaneously work pressure, work autonomy, work environment, and physical evidence have a positive and significant impact on job satisfaction with a significance level of 0.000. . Partial testing for the work pressure variable has a negative effect on job satisfaction, the work autonomy variable has a significant effect on job satisfaction with a significance level of 0.046, the work environment variable has a significant effect on job satisfaction with a significance level of 0.036 and physical evidence has a significant effect on job involvement with a level of significance of 0.049